A Continuous Topography Approach for Agent Based Traffic Simulation, Lane Changing Model - Ade Jamal (Universitas Al Azhar Indonesia, 2014)
Traffic simulation has been being an interesting research subject for transport engineer and scientist, mathematicians and informatics scientist for different point of view. Transport scientists study the traffic complexity and behaviour of traffic participants by using statistical experiment or simulation. The earlier approach was based on macroscopic model deducted from hydrodynamics kinematic wave analogy. Later on the microscopic model was introduced first by invoking cellular automata and then agent based model takes important role in the traffic simulation world. Most of microscopic model are based on a multi-grid element topography model which is a natural environment of cellular automata. Just recently a software engineer started an ambitious work to develop a multipurpose framework for complex traffic simulation. The ingenious idea is to replace the traditional grid based element topography with a continuous two dimensional one from which a region of traffic road or street is built up. Traffic participant is modelled as agent whose physical properties such as its coordinate position, speed, and direction are governed by the kinematic Newtonian law. This article will present this new concept and show how the simple movement of lane changing model that is very well known from the beginning era of traffic simulation become a quite complex movement in the new continuous topography